Localization of gas turbine maintenance by Malaysian gas turbine owners and operators - Amin Abd Majid, M. (Springer Verlag, 2019)
Gas turbines are important equipment for power industry. Local gas turbines are all imported and of various capacities. Among important issues that need to be addressed is to localize the maintenance expertise. Initiatives are being undertaken by the local turbine owners and operators to reduce the imports of the components through localization of refurbishments and parts replacements. This study is to investigate the current practices of localization of gas turbine maintenance works by the Malaysian industry. The study covers gas turbine maintenance practices of the local gas turbine owners and operators and the initiatives undertaken to localize gas turbine maintenance expertise. Potential areas which could enhance the localization of gas turbine maintenance expertise are also highlighted. Â© The Author(s), under exclusive licence to Springer Nature Singapore Pte Ltd. 2019.